Revealing the Enforcement of Mbasuh Dusun Tradition for Pregnant Women Outside of Marriage in Indonesia - Efrinaldi, Efrinaldi; Jayusman, Jayusman; Fatimah, Fatimah; Rimanto, Rimanto; Yarmunida, Miti (Institut Agama Islam Negeri Curup, 2023)
This research aims to reveal the enforcement of the mbasuh dusun tradition in cases of pregnancy outside marriage in Bengkulu City, Indonesia. This type of research is field research. The nature of this research is descriptive analytic. Data collection techniques in this study used observation, interviews, and documentation. The data obtained was analyzed using descriptive qualitative methods to obtain conclusions and research findings. The result of this study is that: the implementation of the mbasuh dusun tradition is a customary sanction for pregnant women outside of marriage in Bengkulu City, as al-'urf al-shahih and has an effective impact. This mbasuh dusun tradition is carried out by slaughtering a goat, and the perpetrator must be present to be aware and must apologize. Then give charity Â (and ask for prayers) at the place where the goat was slaughtered or outside the house. Unlike customary sanctions in other regions, the implementation of the mbasuh dusun tradition has a goal and purpose, so that the perpetrator is ashamed and does not repeat the act again, so that it can effectively reduce and even deter the perpetrator. The application of this customary sanction in the context of developing marriage law in Indonesia, it is necessary to review the legalization of marriage of pregnant women outside of marriage in the Compilation of Islamic Law (KHI), and it turns out that the provision of sanctions for pregnant women outside of marriage has a significant impact on creating a deterrent effect and bringing benefits to the community.Â